Analysis Of The Impact Of Fintech Lending And Kur On The Development Of Micro-Enterprises In Medan City - Lastri Putri Sijabat; Wahyu Ario Pratomo; Irsad Lubis (UNIVED Press, 2024)
This study aims to analyze the relationship between fintech lending and small business loans in providing alternative financial solutions and their impact on the development of micro businesses in Medan. The variables studied include fintech lending and small business loans as independent variables; sales as an intervening variable; and micro business development as a dependent variable. The research data used primary data consisting of 21 subdistricts in Medan City. This study distributed questionnaires to 100 respondents, which were processed using path analysis through the Partial Least Square (PLS) approach. This study was also processed using the Smart-PLS 4 statistical application. The results show that fintech lending and small business loans have a direct, positive and significant effect on sales. Similarly, fintech lending, small business loans, and sales directly have a positive and significant effect on the development of micro businesses in Medan City. In addition, fintech lending and small business loans indirectly increase the development of micro businesses in Medan City through sales.